2016
DOI: 10.25336/p6801v
|View full text |Cite
|
Sign up to set email alerts
|

Trends, patterns, and differentials in Canadian mortality over nearly a century, 1921-2011

Abstract: In the past 90 years, remarkable progress has been made in substantially improving survival and longevity in Canada, establishing it among today's group of very low mortality countries. We use several demographic indicators of all-cause and cause-specific mortality to illustrate the nature of these major advances throughout the lifespan. Reviewing the literature on trends in Canadian mortality, we also uncover various challenges for the decades to come. Reducing or even eliminating important disparities in mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 59 publications
1
2
0
Order By: Relevance
“…This study confirms an immigrant health advantage pertaining to mortality, 7-9 and corroborates the historical Canadian trend of a female mortality advantage. 26 Also, the advantage in all-cause and premature mortality among male immigrants over male long-term residents was slightly more pronounced than the advantage among female immigrants over female long-term residents; consistent with previous studies. 7 9 We found that the immigrant and female mortality advantage extended to causes of death amenable to public health and medical care.…”
Section: Discussionsupporting
confidence: 90%
“…This study confirms an immigrant health advantage pertaining to mortality, 7-9 and corroborates the historical Canadian trend of a female mortality advantage. 26 Also, the advantage in all-cause and premature mortality among male immigrants over male long-term residents was slightly more pronounced than the advantage among female immigrants over female long-term residents; consistent with previous studies. 7 9 We found that the immigrant and female mortality advantage extended to causes of death amenable to public health and medical care.…”
Section: Discussionsupporting
confidence: 90%
“…However, the cause of death in the Canadian Vital Statistics has been used widely in research recently. [31][32][33][34][35] Finally, this study is observational in nature and subject to inherent limitations of this study design, such as misclassification and unobserved confounders, which may affect results.…”
Section: Study Limitationsmentioning
confidence: 99%
“…Moreover, Canada's age-specific mortality rate for both sexes combined rose, from 7.0 per 1000 population in 1991 to 7.6 in 2019 (Statistics Canada, Table 13a [2]). Bourbeau and Quellette [3] gave an excellent historical summary of mortality trends and patterns in Canada from 1921 to 2011, demonstrating the country's remarkable achievement in mortality management and efforts to promote health. In addition, there is literature on the epidemiology of population change due to cause-of-death analysis (Bah and Rajulton [4]) and changes in life-expectancy (Bourbeau [5]; Lussier et al [6]) for an overview see Mandich and Margolis [7].…”
Section: Introductionmentioning
confidence: 99%